ANALYSIS OF SERVICE QUALITY, STORE ATMOSPHERE, AND PRICE DISCOUNTS ON IMPULSE BUYING AT MATAHARI CONSUMERS DEPARTMENT BINJAI SUPERMALL STORE - Indawati Lestari (SEAN Institute, 2023)
The aim study this is to know and analyze the influence of quality service, store atmosphere, and discounts price against impulse buying. Study this made to consumers Sun Department Store Binjai Supermall. Population in a study this is visiting consumers Sun Department Store Binjai Supermall. Withdrawal sample use sample accidental as many as 200 respondents. Data analysis performed is multiple linear regression using the SPSS program. The results of data analysis show that in a manner Partial variable quality service, store atmosphere, and discounts price significantly influence impulse buying on consumers Sun Department Store Binjai Supermall.